2003
DOI: 10.2337/diabetes.52.11.2767
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Glucose in Rat Ventromedial Hypothalamus During Acute and Recurrent Hypoglycemia

Abstract: The activity of neurons in the ventromedial hypothalamus (VMH) important for initiating compensatory responses to hypoglycemia is influenced by ambient glucose concentration. In the present study, we used in vivo microdialysis to evaluate interstitial glucose concentrations in rat VMH under various glycemic conditions. Using the zero-net-flux method, steady-state glucose concentration in the VMH was ϳ20% of blood glucose (ϳ1.4 mmol/l) in fed rats but ϳ14% of blood glucose (ϳ0.7 mmol/l) in overnight-fasted rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(170 citation statements)
references
References 53 publications
(53 reference statements)
9
159
0
2
Order By: Relevance
“…In addition to the sleep studies noted above, rodent models have proven useful in elucidating the neurobiological and neuropathological changes after recurrent hypoglycemia, a common complication of insulin-treated diabetes [9,44]. A limitation of the rodent model for hypoglycemia studies is the difficulty in assessing hypoglycemic symptoms that indicate the presence of hypoglycemia awareness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the sleep studies noted above, rodent models have proven useful in elucidating the neurobiological and neuropathological changes after recurrent hypoglycemia, a common complication of insulin-treated diabetes [9,44]. A limitation of the rodent model for hypoglycemia studies is the difficulty in assessing hypoglycemic symptoms that indicate the presence of hypoglycemia awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, neural pathways stimulated by hypoglycemia induce feeding behavior [2]. Hormone responses and symptoms of hypoglycemia tend to be blunted in DM patients treated with insulin, and it is likely that deficient responses to hypoglycemia result from recurrent severe hypoglycemia sustained over many years of insulin replacement [1] CNS mechanisms of autonomic and endocrine responses to hypoglycemia have been studied in dogs and in rodents, and these studies indicate participation of structures in brainstem as well as hypothalamus [3][4][5][6][7][8][9][10][11][12]. Although these animal studies have proven useful in elucidating aspects of neural circuitry underlying counterregulatory hormone secretion, symptom thresholds, per se, cannot be directly assessed in an animal model.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is still unclear how GK, with its high K m , might mediate neuronal glucosensing at physiological brain glucose levels (4,10,11). Like the ␤-cell, which expresses a similar isoform of GK but not GKRP (27,32), glucosensing neuron GKRP expression was too infrequent for it to be a significant regulator of GK activity that might bring the functional K m of GK activity down to appropriate brain glucose levels (11,12,63). There are also several differences between GE neurons and pancreatic ␤-cells.…”
Section: Characterization Of Vmn Glucosensing Neuronsmentioning
confidence: 99%
“…A Neurobasal-A media, devoid of glucose and pyruvate (NB-A f ), allowed for the control of glucose concentrations. We supplemented NB-A f with B27 and either a non-physiological high glucose concentration of 25 mM (NB-A 25 ), or 3 mM (NB-A 3 ), a physiological glucose concentration for the brain (Silver, et al, 1994;Abi-Saab, et al, 2002;de Vries, et al, 2003) (Fig. 1A).…”
Section: Restorative Feedings Reduce Fluctuations In Ambient Glucose mentioning
confidence: 99%
“…Extracellular glucose concentrations in rodent and human brain are closely coupled to plasma glucose concentrations (Silver, et al, 1994;Abi-Saab, et al, 2002;de Vries, et al, 2003). In euglycemia, plasma glucose can range from 5.5 to 7.8 mM, while brain glucose fluctuates from 0.82 to 2.4 mM, depending on the microdialysis method employed (Silver, et al, 1994;Abi-Saab, et al, 2002;de Vries, et al, 2003). Using glucose microelectrodes to continuously monitor changes in glucose concentrations it has been demonstrated that the extracellular glucose concentration in the brain is altered dramatically during hyper-and hypoglycemia, in which plasma levels may reach 15.2 mM or drop to 2.8 mM, respectively.…”
Section: Introductionmentioning
confidence: 99%